Enhancing Entrepreneurial Orientation among Women: A Multi Regression Approach - Latiyan, Anshu; Ghai, Sachin; Mishra, Amar Kumar; Kahera, Roopika (Journal of Reliability and Statistical Studies, 2024)
The survival, growth and prosperity of any region depend upon its economy. While the government undertakes every step it can take to boost the economy of a region, it cannot uplift the economy alone. The entrepreneurs play a pivotal role in assisting the government in completing this Herculean task. The contribution of entrepreneurs is even more significant in small states like Uttarakhand, which is still in its nascent state after being carved out in 2000 as the 27th state of India. The hilly terrains, remoteness from the center, and extreme climate all contribute to making its economy more contingent upon the entrepreneurial ventures of the indigenous people. While there is a surge of entrepreneurial activities in urban areas close to the plains, there is a dearth of such endeavors in the hilly areas. The situation is graver in the rural areas of the hilly region, especially for women as most of them lack awareness, resources and support and are primarily engaged in agricultural and husbandry activities. A paradigm change is required for the inclusion of such women for the holistic and heuristic development of the economy. This demands a shift from an agrarian to an entrepreneurial civilization. However, entrepreneurial orientation cannot be developed overnight and in isolation. It requires the instillation of personality characteristics. In the present paper, the researchers have identified three personality variables: – self-esteem, self-efficacy, and locus of control as the antecedents of entrepreneurial orientation and, using multiple regression, have explored the contribution of these personality variables to entrepreneurial orientation among women in the hilly region of Uttarakhand. The data for the present study were collected using stratified sampling and structured questionnaires from 200 women in the age group of 18 years to 40 years. The finding revealed that the personality variables accounted for 66.5 % of the variation in entrepreneurial orientation. Further, it also revealed that locus of control (LOC) contributed most to the development of entrepreneurial orientation (EO), followed by self-efficacy and self-esteem.